Sociotechnical Challenges of Developing an Interoperable Personal Health Record - Gaskin, G.L.; Longhurst, C.A.; Slayton, R.; Das, A.K. (Applied Clinical Informatics, 2011)
Objectives: To analyze sociotechnical issues involved in the process of developing an interoperable commercial Personal Health Record (PHR) in a hospital setting, and to create guidelines for future PHR implementations.Methods: This qualitative study utilized observational research and semi-structured interviews with 8 members of the hospital team, as gathered over a 28 week period of developing and adapting a vendor-based PHR at Lucile Packard Children’s Hospital at Stanford University. A grounded theory approach was utilized to code and analyze over 100 pages of typewritten field notes and interview transcripts. This grounded analysis allowed themes to surface during the data collection process which were subsequently explored in greater detail in the observations and interviews.Results: Four major themes emerged: (1) Multidisciplinary teamwork helped team members identify crucial features of the PHR; (2) Divergent goals for the PHR existed even within the hospital team; (3) Differing organizational conceptions of the end-user between the hospital and software company differentially shaped expectations for the final product; (4) Difficulties with coordination and accountability between the hospital and software company caused major delays and expenses and strained the relationship between hospital and software vendor.Conclusions: Though commercial interoperable PHRs have great potential to improve healthcare, the process of designing and developing such systems is an inherently sociotechnical process with many complex issues and barriers. This paper offers recommendations based on the lessons learned to guide future development of such PHRs.
Keywords: Personal health records; medical records; information systems; sociotechnical analysis